Postpartum ovarian activity in Sahiwal - Friesian cows fed different levels of energy - Mohd. Adam, Azillah (1984)
Postpartum ovarian function was determined by milk progesterone radioimmunoassay in 21 first-calf Sahiwal-Friesian cows assigned to one of three treatment groups designated as low, medium and high energy levels (n=7). The progesterone concentrations in defatted milk were determined thrice weekly for 120 days postpartum. Mean interval to resumption of ovarian activity and to forst ovulation was longest in the low energy group and shortest in the high energy group. Using progesterone concentration of > 1 ng/ml as criteria for corpus luteum activity, first ovulation occurred at 37.7 ± 18.0,26.6;t 15.7and25.3 ± 8.4 days for low, medium and high energy groups, respectively. However, first estrus was observed at 28.0 ± 21.6, 32.7:t 9.8 arid 25.4:t 6.0 days, respectively. The percentages of silent estrus were 13.6 percent, 29.6 percent and 14.3 percent for low, medium and high energy groups, respectively, with a majority ( 46.7 percent) detected during the initial postpartum estrous cycle. Interval to first insemination was longest in the low energy group, being 68.6·± 10.3,62.6 ± 18.1 and 56.6 ± 8.1 days for lOIN, medium and high energy groups, respectively. However, services per conception were 1.1, 1.7 and 3.3, respectively. Interval to conception was shortest in the low energy group, being 74.3 ± 14.9, 79.1 ± 17.3 and 88.3 ± 30.4 days for low, medium and high energy groups, respectively. The corresponding first service conception rates were 85.7 percent, 42.9 percent and 42.9 percent. Although a trend was detected, the differences were not statistically significant (p> 0.05) between the groups on the reproductive parameters analysed. In summary, low energy intake may delay the resumption of postpartum ovarian activity and ovulation in Sahiwal-Friesian cows. Mean interval from calving to conception, however, was not significantly different amongst the three groups if breeding commenced after 60 days postpartum. A higher incidence of silent estrus was detected during the initial estrous cycles after calving. Lastly, milk progesterone radioimmunoassay is a useful tool for estrus confirmation, early pregnancy diagnosis and assessment of fertility in postpartum cows.